Karakteristik Prososial Anak Autis Usia Dini di Kupang - Jendriadi Banoet; Beatriks Novianti Kiling-Bunga; Indra Yohanes Kiling (Universitas Trunojoyo Madura, 2016)
Attendance rates of children with disabilities are predicted to be lower than other children. Especially for the young children with disabilities. Besides of the reason that it is not easy to detect the disability from earlier, there are not many institutions that provided specialized programs for young children with special needs, one of them is children with autism. This research aims to describe prosocial characteristics of young children with autism. Employed approach were qualitative with observation and interview as the data gathering techniques. Results shown that young children with autism showed prosocial behaviour patterns that is expression from mimicking teacher or parent, able to greet friends when directed by teacher and parent, willing to socialize with other persons, and showing participation in a group as in working together and behaving according to norms, even though all mentioned behaviours were directed by teacher and parent